Analisis Sistem Autentikasi Dua Faktor (2FA) Dan Efektivitasnya Dalam Meningkatkan Keamanan Akses - Azkal Azkiya; Muhammad Budi Prayoga Ichsan; Nabil Azhari Putra Finula Hasibuan; Reva Andrianti; Intan Maulana (JIKUM: Jurnal Ilmu Komputer, 2026)
The rapid development of information technology has led to an increase in security threats to digital systems, particularly in user authentication mechanisms. Single-factor authentication based solely on passwords is no longer sufficient to protect system access from attacks such as phishing, brute force, and credential stuffing. Therefore, two-factor authentication (2fa) has emerged as a solution by adding an additional layer of security. This study aims to analyze the concept of 2fa and evaluate its effectiveness in improving system access security. The research method used is a literature study of various studies and implementations of 2fa in modern information systems. The results indicate that the implementation of 2fa significantly reduces the risk of unauthorized access and increases user trust in system security, despite challenges related to usability and technical implementation.